Analysis of human capital for infrastructure development relation to industrialization in Indonesia - Afrianti, Nur Lailah; Syafitri, Syafitri; Anisa, Muni; Bintang, Khairil Insan (Universitas Ahmad Dahlan, 2024)
This research aims to analyze the value-added between infrastructure and industrialisation in Indonesia and both as critical aspect that supports the achievement of 9 Sustainable Development Goals (SDG). SDG 9 focuses on building durable infrastructure, promoting inclusive and sustainable industrialisation, and encouraging innovation. This research focuses on analyze the impact of infrastructure on the level of industrialisation, taking into account the modulation by human capital. Data analysis was conducted using Stata version 16 software with the aim of testing the direct impact of variables as well as testing the indirect impact through the application of the Sobel test. The Sobel test aims to analyse the dataset from 1990-2022. This research specifically explores the Indonesian context as a case study, identifying infrastructure variables that are significant in shaping the level of industrialisation in the country. In addition, this research involves an in-depth analysis of the role of human capital in moderating the impact of infrastructure on the level of industrialisation. The significance of this research lies in its potential to address critical knowledge gaps in understanding the complex interplay between infrastructure development, industrialization, and economic growth in Indonesia. The implication of the study that investment on infrastructure for industrialization can absorb labor.